Interaction of Intestinal Microorganisms with the Human Host in the Framework of Autoimmune Diseases - Sánchez, Borja; Hevia, Arancha; González, Sonia; Margolles, Abelardo (Frontiers in Immunology, 2015)
Autoimmune diseases such as Systemic Lupus Erythematosus (SLE) are caused by a complex interaction of environmental, genetic, and sex related factors. Although SLE has traditionally been considered as independent from the microbiota, recent work published during the last 5 years suggests a strong connection between SLE and the composition of our gut commensals as one of the main environmental factors linked to this disease. Preliminary data has evidenced that i) interaction of certain microbial-derived molecules with specific cell receptors, and ii) the influence of certain commensal microorganisms over specific immune cell subsets, play an important role in the pathogenesis of SLE and SLE-like diseases. In addition, epigenetic changes driven by certain microbial groups have been recently proposed as an additional link between gut microbiota and SLE. As immune responses elicited against commensal bacteria are deeply dependent on the composition of the latter, and as microbial populations can be modified by dietary interventions, identifying the precise gut microorganisms responsible for worsening the SLE symptoms is of crucial importance for this and other SLE-related diseases, including antiphospholipid syndrome or lupus nephritis. In this minireview, the current knowledge on the relationships between microbes and SLE and SLE-related diseases is compiled and discussed.